Meningkatkan Konsep Diri Penderita Kusta Melalui Social Care - Hamim, Nur; Sunanto, Sunanto; Mariani, Mariani (STIKES Yayasan RS.Dr.Soetomo, 2023)
Infectious diseases were prevalent in developing countries that have low socio-economic conditions. One such infectious disease is leprosy. Leprosy is generally contained in the country - a country that is growing as a result of the limitations of the country's ability to provide adequate services in the areas of health, education, and socio-economic welfare of society, leprosy samapai is still feared by the people, the family, including some health workers, Health officials are thus due to lack of knowledge, understanding, and the erroneous belief perhaps leprosy and disabilities caused. Leprosy Indonesia ranks -4 after India, Brazil, and Nepal. Indonesia within the last ten years (until December 2015) has managed to show leprosy morbidity rates around 85%, ie from 107.271 17.137 people. Based on the results obtained in the activities pengabidian Society in Galagah, the management of Social Care in improving Self Concept of Leprosy There is a good understanding of the concept of self so that they can socialize with other public so there is no curtain or skating to do all of society mingle with all components other society. Creation of a balance between the duties and functions of the family in supporting family members who suffer from leprosy. There are understanding aspects - aspects of social care and self-concept cover physical, psychological, social, and environmental lepers.